Ocular Manifestations of COVID-19 Infection - Das, Himasri; Arif, Syed A.; Goswami, Chandrani; Das, Tinku; Deka, Deepjyoti; Ali, Arfan; Gogoi, Sophia M.; Bora, Durlav P. (International Journal of Bio-resource and Stress Management, 2022)
The eyes, which were not previously the subject of investigation, have emerged as one of the more intriguing aspect of COVID-19 infection. The probable pathways for SARS-CoV-2 infection through the eyes are either through the tear film and draining tear ducts leading to the upper respiratory tract and gastrointestinal tract, or through the conjunctiva into limbal superficial cells into the inner eye, where distribution via the blood or nervous system appears to be possible. Virus pathogenesis through tear and conjunctiva has been established in animal models of several coronavirus eye diseases, and preliminary research have shown that SARS-CoV-2 may do the same in humans. Given that COVID-19 cases have reached pandemic proportions and are on the rise, it is vital to recognize the illness’s ocular manifestations and avert potentially vision-threatening effects. Coronaviruses may be transmitted between animals and humans through evolution, therefore investigating them in animal models could be crucial in the future to discover further elements of ocular involvement. It is recommended that health care and individual personnel take steps to avoid infection and limit viral transmission. More study is needed to understand the transmission pathways and the alternatives for COVID-19 prevention and therapy disseminated through the ocular surfaces for prompt recovery of the patients.